AKIBAT HUKUM TERHADAP PEMBATALAN PERKAWINAN SECARA FASAKH - Shavira, Elita Dwi (Journal of Law ( Jurnal Ilmu Hukum ), 2018)
AbstractMarriage is a sacred thing for humans who live it, with the aim of forming a harmonious family that can form a happy atmosphere towards the realization of tranquility, comfort for husband and wife and family members.a marriage that occurs when the marriage breaks up either because of divorce, khulu or other causes such as the breaking up of a marriage bond because of course cancellation there are legal consequences that arise both to the relationship of husband and wife, property and children.the need for more stringent supervision in the implementation of marriage and guidance to the community so that in the implementation of marriage there are no rules that are violated so that it can cause harm to him and others.